Stan wiedzy studentów Uniwersytetu Ekonomicznego we Wrocławiu z zakresu systemów zarządzania jakością - Kowalczyk, Marta; Lesiów, Tomasz (Knowledge Analysis of Students from the University of Economics in Wrocław in the Range of Quality Management Systems, 2008)
The role of education in training future manager staff in the scope of functioning of the HACCP system and quality management system was examined. On the example of students from the Wroclaw University of Economics it was checked if obligatory subjects concerning quality and quality management would influence the broadening of their knowledge and awareness about this topic. Students from the department where the subject quality management is carried out had a very good knowledge concerning HACCP and ISO 9001. Students from the department that up to 2007 did not offer courses on quality management had lower knowledge concerning quality systems what was the reason for the need of their additional education after completing university.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 82-94